(untitled) (Nordic Journal of African Studies, 2003)
This paper examines the contributions of pressure groups to democratic process in Nigeria. The paper attempts a conceptualization of pressure groups and democracy. It also examines the relevance of pressure groups generally as well as their attitude to and participation in the democratic process particularly. The specific contributions of these groups to democratic process as well as obstacle to their effectiveness are discussed. The paper concludes by advocating the need for the groups to have wider spread and to participate more actively in the democratic process, among others as ways of being more relevant in democratic process.